Robust clinical detection of SARS‐CoV‐2 variants by RT‐PCR/MALDI‐TOF multitarget approach. Issue 4 (16th December 2021) - Hernandez, Matthew M.; Banu, Radhika; Gonzalez‐Reiche, Ana S.; van de Guchte, Adriana; Khan, Zenab; Shrestha, Paras; Cao, Liyong; Chen, Feng; Shi, Huanzhi; Hanna, Ayman; Alshammary, Hala; Fabre, Shelcie; et al.
Abstract: The coronavirus disease 2019 (COVID‐19) pandemic has sparked the rapid development of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) diagnostics. However, emerging variants pose the risk for target dropout and false‐negative results secondary to primer/probe binding site (PBS) mismatches. The Agena MassARRAY® SARS‐CoV‐2 Panel combines reverse‐transcription polymerase chain reaction and matrix‐assisted laser desorption/ionization time‐of‐flight mass‐spectrometry to probe for five targets across N and ORF1ab genes, which provides a robust platform to accommodate PBS mismatches in divergent viruses. Herein, we utilize a deidentified data set of 1262 SARS‐CoV‐2‐positive specimens from Mount Sinai Health System (New York City) from December 2020 to April 2021 to evaluate target results and corresponding sequencing data. Overall, the level of PBS mismatches was greater in specimens with target dropout. Of specimens with N3 target dropout, 57% harbored an A28095T substitution that is highly specific for the Alpha (B.1.1.7) variant of concern. These data highlight the benefit of redundancy in target design and the potential for target performance to illuminate the dynamics of circulating SARS‐CoV‐2 variants. Highlights: SARS‐CoV‐2 variation introduces mismatches at diagnostic primer/probe sites. A multi‐target RT‐PCR/MALDI‐TOF assay captures emergent variants in NYC patients. Paired sequencing data reveals the Alpha‐specific A28095T causes target dropout. Diagnostic target performance illuminates dynamics of circulating SARS‐CoV‐2.